Ship Operation Technology Reference Book and Guidebook - Pfaff, Manfred; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2022)
This technical book presents in a concise and concentrated form all the essential aspects of operating a ship. These include the basics of buoyancy and propulsion technology, ship safety, occupational safety and environmental protection on board as well as important auxiliary equipment. These aspects are explained in more detail using numerous examples. The book is intended for ship's engineers at university, on board and in shipping companies as well as for design engineers in the shipyard. This book is a translation of the original German 1st edition Schiffsbetriebstechnik by Manfred Pfaff, published by Springer Fachmedien Wiesbaden GmbH, part of Springer Nature in 2018. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors. The contents Job description of the marine engineer - Rules and regulations - Hull, ropes, superstructures, anchor gear, corrosion protection and deck coverings - Propulsion systems - Ship operating systems/auxiliary systems - On-board power supply and electrical circuit examples - Occupational safety and ship safety, fire protection - Environmental protection in maritime shipping The target groups - Students of marine engineering - Lecturers and assistants at universities and technical colleges in the field of marine engineering - Engineers and masters in shipyards, technical personnel on ships of the navy and Christian seafaring - Nautical officers, technical staff in shipping companies and people interested in technology in general The Author Dr. - Eng. Manfred Pfaff, naval engineering reserve officer in the German Navy, received his doctorate from the Faculty of Mechanical and Marine Engineering at the University of Rostock. He is currently employed as head of waste flow control at the Detmold district government.
Job description of the marine engineer -- regulations -- hull, ropes, superstructures, anchor gear, corrosion protection and deck coverings -- propulsion systems -- ship operating systems/auxiliary systems -- on-board power supply and electrical circuit examples -- occupational safety and ship safety, fire protection -- environmental protection in maritime shipping.
Keywords: Transportation engineering; Traffic engineering; Transportation Technology and Traffic Engineering; Ships; Ship propulsion; Shipbuilding